2020
DOI: 10.1016/j.bone.2019.115173
|View full text |Cite
|
Sign up to set email alerts
|

The risk of hip and non-vertebral fractures in patients with Parkinson's disease and parkinsonism: A systematic review and meta-analysis

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder that is common in older individuals. PD patients have an increased risk of fractures compared to the general population, perhaps due to multiple falls. However, the fracture risk has not been fully assessed. To assess the impact of PD on the risk of hip and non-vertebral fractures, we conducted a systematic review and meta-analysis. Comprehensive searches of three key bibliographic databases were conducted to identify reviews and primary studies relating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 47 publications
(76 reference statements)
3
14
0
Order By: Relevance
“…Although in a young healthy individual, a fall from standing height would not likely result in a fracture, in PD, reduced bone mineral density (150)(151)(152) and a higher frequency of falls increase fracture risk (43,(153)(154)(155)(156)(157)(158)(159) . Studies suggest that in PD, osteoporosis and fracture are twice as likely (150,160,161) , and in women, PD is the strongest single contributor to fracture risk (162) .…”
Section: Malnutrition Muscle and Bonementioning
confidence: 99%
“…Although in a young healthy individual, a fall from standing height would not likely result in a fracture, in PD, reduced bone mineral density (150)(151)(152) and a higher frequency of falls increase fracture risk (43,(153)(154)(155)(156)(157)(158)(159) . Studies suggest that in PD, osteoporosis and fracture are twice as likely (150,160,161) , and in women, PD is the strongest single contributor to fracture risk (162) .…”
Section: Malnutrition Muscle and Bonementioning
confidence: 99%
“…Parkinson disease (PD) patients are susceptible to recurrent falls 1 - 3 and subsequent hip fractures. 1 , 2 , 4 - 8 They exhibit a 3-fold risk of falls compared to the general population, 3 with more than 50% sustaining repeated falls. 1 , 2 Of those that fall, approximately 1/3 sustain 1 or more fractures, with 28-50% of such fractures involving the hip.…”
Section: Introductionmentioning
confidence: 99%
“…People with Parkinson's disease (PD) have a high risk of fracture that may be due, in large part, to their high risk of multiple falls and impaired reflexes to protect against injury during a fall. A recent systematic review and meta-analysis found that people with PD, based on data from health systems and self-report, have a 2.35-fold increased risk of hip and 1.8-fold increased risk of all fractures besides vertebral fractures 1 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%